2014
DOI: 10.1212/wnl.0000000000000041
|View full text |Cite
|
Sign up to set email alerts
|

Tongue pressure as a novel biomarker of spinal and bulbar muscular atrophy

Abstract: Tongue pressure measurement is reliable and reflects swallowing function in patients with SBMA. The muscle strength of the tongue appears to decrease in SBMA before the awareness of subjective dysphagia, suggesting that tongue pressure measurement is a novel biomarker of SBMA and is applicable to early-stage detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 32 publications
4
67
0
Order By: Relevance
“…Some previous surveys have also used the time of 7 seconds (1,21) , whereas others have used a shorter time, between two and three seconds (19,22,26,28) , but these studies that used shorter contraction times evaluated only maximum tongue force, whereas the present study also assessed mean tongue force. In order not to obtain results with variations caused by muscle fatigue, a rest period was observed between measurements; as in previous studies, this time was one minute (1,13,(21)(22)(23)(24) . In addition to the good reproducibility of the data, it is worth noting that the software that accompanies the Forling instrument is easy to use, enabling modification of the data recording time and data visualization during measurement, allowing the instrument to be used in different ways and without need of extensive training.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Some previous surveys have also used the time of 7 seconds (1,21) , whereas others have used a shorter time, between two and three seconds (19,22,26,28) , but these studies that used shorter contraction times evaluated only maximum tongue force, whereas the present study also assessed mean tongue force. In order not to obtain results with variations caused by muscle fatigue, a rest period was observed between measurements; as in previous studies, this time was one minute (1,13,(21)(22)(23)(24) . In addition to the good reproducibility of the data, it is worth noting that the software that accompanies the Forling instrument is easy to use, enabling modification of the data recording time and data visualization during measurement, allowing the instrument to be used in different ways and without need of extensive training.…”
Section: Discussionmentioning
confidence: 93%
“…They were instructed about the operation of the instrument and requested to insert the mouthguard into their oral cavity comfortably. The examiner then waited 15 seconds for participants to get used to mouthguard and instructed them to protrude the tongue with the greatest possible force upon request, triggering the device that measures the tongue force for seven seconds (1,21) ; participants had no access to the test results. All instrumental assessments were conducted by the same previously trained examiner.…”
Section: Thismentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that tongue pressure may serve as a marker of swallowing function at an early stage of SBMA 29. VFSS enables visualization of the swallowing movement, while tongue pressure assesses a part of the swallowing function.…”
Section: Discussionmentioning
confidence: 99%
“…Significant changes in grip strength have been observed in a 3-year longitudinal study of SBMA patients [107] but no significant change over a one year period was detected in another study [103]. A recent study evaluated the measure of tongue pressure using an intraoral pressure probe [108]. This measure seems to be reliable but longitudinal studies are required to confirm its use as biomarker of disease progression.…”
Section: Biomarkersmentioning
confidence: 99%